Comparative genomics of Beauveria bassiana: uncovering signatures of virulence against mosquitoes. (December 2016) - Valero-Jiménez, Claudio; Faino, Luigi; Spring in't Veld, Daphne; Smit, Sandra; Zwaan, Bas; van Kan, Jan
Abstract Background Entomopathogenic fungi such asBeauveria bassiana are promising biological agents for control of malaria mosquitoes. Indeed, infection withB. bassiana reduces the lifespan of mosquitoes in the laboratory and in the field. Natural isolates ofB. bassiana show up to 10-fold differences in virulence between the most and the least virulent isolate. In this study, we sequenced the genomes of five isolates representing the extremes of low/high virulence and three RNA libraries, and applied a genome comparison approach to uncover genetic mechanisms underpinning virulence. Results A high-quality, near-complete genome assembly was achieved for the highly virulent isolate Bb8028, which was compared to the assemblies of the four other isolates. Whole genome analysis showed a high level of genetic diversity between the five isolates (2.85–16.8 SNPs/kb), which grouped into two distinct phylogenetic clusters. Mating type gene analysis revealed the presence of either theMAT 1–1–1 or theMAT 1–2–1 gene. Moreover, a putative newMAT gene (MAT 1-2–8) was detected in theMAT 1–2 locus. Comparative genome analysis revealed that Bb8028 contains 163 genes exclusive for this isolate. These unique genes have a tendency to cluster in the genome and to be often located near the telomeres. Among the genes unique to Bb8028 are a Non-Ribosomal Peptide Synthetase (NRPS) secondary metabolite gene cluster, a polyketide synthase (PKS) gene, and five genes with homology to bacterial toxins. A survey of candidate virulence genes forB. bassiana is presented. Conclusions Our results indicate several genes and molecular processes that may underpin virulence towards mosquitoes. Thus, the genome sequences of five isolates ofB. bassiana provide a better understanding of the natural variation in virulence and will offer a major resource for future research on this important biological control agent.